HAS THE COVID 19 PANDEMIC AFFECT THE WORLD EQUALLY? - Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2021)
Rich and powerful people have built a new system in which only risk is common, and profit is exclusively theirs. Neoliberalism is an ideology that is realized in the interest of the rich and powerful. They have enormous financial (and not only financial) power by which they shape the political, media and (quasi) scientific space in order to conduct economic policy and publicly promote the values ​​that suit them. That is why in recent years we have mostly heard that the problem has arisen because people do not live in accordance with the real possibilities and that we must continue to tighten our belts and rationalize our jobs (translated from Orwell's new speech: further dismissals of employees). Much less is said about the problem of inequality, i.e. uneven and unjust distribution and concentration of wealth, and that a solution should be sought there. The latest economic crisis caused by COVID / 19 has shown that not everyone is equally affected by the crisis: the rich have become even richer and the poor have become even poorer. This paper will discuss the unequal consequences caused by the latest pandemic crisis.
Keywords: pandemic; inequality; economy; markets; business systems